Fine particle sources and cognitive function in an older Puerto Rican cohort in Greater Boston. Issue 3 (September 2018) - Wurth, Renee; Kioumourtzoglou, Marianthi-Anna; Tucker, Katherine L.; Griffith, John; Manjourides, Justin; Suh, Helen
Abstract : Background: Puerto Ricans living in the mainland US have substantially higher rates of impairment to cognitive performance as compared to non-Hispanic Whites, with air pollutant exposures a potential risk factor. We investigated whether exposures to specific air pollution sources were associated with performance across several cognitive domains in a cohort of Puerto Rican older adults. Objectives: To investigate the association between sources of fine particulate matter (PM2.5 ) and cognitive performance in each of five cognitive domains. Methods: We obtained demographic, health, and cognitive function data for 1500 elderly participants of the Boston Puerto Rican Health Study. Cognitive function was assessed in each of two waves for five domains: verbal memory, recognition, mental processing, and executive and visuospatial function. To these data, we linked concentrations of PM2.5 and its components, black carbon (BC), nickel, sulfur, and silicon, as tracers for PM2.5 from traffic, oil combustion, coal combustion, and resuspended dust, respectively. Associations between each PM2.5 component and cognitive domain were examined using linear mixed models. Results: One year moving average exposures to BC were significantly associated with decreased verbal memory (−0.38; 95% confidence interval [CI] = −0.46, −0.30), recognition (−0.35; 95% CI = −0.46, −0.25), mental processing (−1.14; 95% CI = −1.55, −0.74), and executive function (−0.94; 95% CI = −1.31, −0.56). Similar associations were found for nickel. Associations for sulfur, and silicon, and PM2.5 were generally null, although sulfur (−0.51; 95% CI = −0.75, −0.28), silicon (−0.25; 95% CI = −0.36, −0.13), and PM2.5 (−0.35; 95% CI = −0.57, −0.12) were associated with decreased recognition. Conclusion: Long-term exposures to BC and nickel, tracers of traffic and oil combustion, respectively, were associated with decreased cognitive function across all domains, except visuospatial function. Abstract : Supplemental Digital Content is available in the text.